2016
DOI: 10.12688/f1000research.9131.2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior single odontoid screw placement for type II odontoid fractures: our modified surgical technique and initial results in a cohort study of 15 patients

Abstract: Objective: Anterior odontoid screw fixation for type II odontoid fracture is the ideal management option. However in the context of unavailability of an O-arm or neuro-navigation and poor images from the available C-arm may be an obstacle to ideal trajectory and placement of the odontoid screw. We herein detail  our surgical technique so as to ensure a correct trajectory and subsequent good fusion in Type II odontoid fractures. This may be advantageous  in clinical set ups lacking state of the art facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We created a small gutter on the superior aspect of C3 body like as Sunil Munakomi et al technique, by this method we ensure accurate placement of the odontoid screw behind the anterior cortex of C2 body without deviation from midline. The groove also provides the proper shelter for the screw head avoiding damage to the eosephagus (Munakomi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We created a small gutter on the superior aspect of C3 body like as Sunil Munakomi et al technique, by this method we ensure accurate placement of the odontoid screw behind the anterior cortex of C2 body without deviation from midline. The groove also provides the proper shelter for the screw head avoiding damage to the eosephagus (Munakomi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…where 60% of their cases had RTA [22]. and 80% of patients included in Wilson study presented after RTA [23].…”
Section: Discussionmentioning
confidence: 99%
“…One titanium lag screw was inserted in all cases and this was wise enough in starting up experience .in addition, bone quality was fine as most patients where below 50 years with no history of bone quality affecting diseases. Sunil et al [22] also inserted one screw in all cases, while Dailey et al found that putting 2 screws enhance better fusion but their cases were older than 70 years [24]. And this may explain their need to assure fixation due to possible weak bone quality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 13 ] In contrast, posterior internal atlantoaxial fixation and fusion are indicated for Type IIC fractures that extend anteroinferior to posterosuperior, comminuted fractures, concomitant disruption of the transverse ligament, fractures that are nonreducible or do not maintain adequate alignment, and as a salvage procedure for inadequate healing following conservative treatment or AOSF failure. [ 5 , 8 , 10 , 13 , 20 - 22 , 25 , 28 , 29 , 33 , 36 , 40 ] Displacement of the dens of ≥6 mm and angulation of ≥10° has been associated with a higher rate of nonunion after conservative treatment, as well as AOSF surgical failure, and, thus, is also indications for posterior surgical treatment. [ 12 , 20 , 22 , 24 , 25 , 28 , 44 ] Additional risk factors for AOSF surgical failure include fracture age postinjury of 6 months or greater, as the chance of success for stabilization and osteosynthesis decreases, as well as a fracture gap of >2 mm.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In patients with significantly reduced bone mineral density, strength, and healing potential, as seen in patients with severe osteoporosis, attaining adequate fixation and fusion are challenging and considered a contraindication given the high possibility for nonunion. [ 1 , 8 , 23 , 29 , 40 ] Body habitus must also be heavily considered, as obesity and structural deformities can impose limitations that may interfere with surgical execution and outcome. A fixed cervical spine with inability to impose neck extension or moderate-to-severe thoracic kyphosis, a short neck, or a barrel-shaped chest restricts proper patient positioning and access to the anterior neck, contraindicating AOSF as a surgical approach.…”
Section: Patient Selectionmentioning
confidence: 99%